1984
DOI: 10.1148/radiology.152.1.6233632
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial perfusion scintigraphy with Tc-99m-MAA. Use of a totally implanted drug delivery system.

Abstract: Tc-99m-MAA hepatic arterial perfusion scintigraphy ( HAPS ) using a totally implanted drug delivery system was employed for hepatic arterial chemotherapy in 147 patients (335 studies). Complete perfusion of the involved liver was seen in 88% of patients initially [more so in those with normal hepatic vascular anatomy (93%) than those with vascular variants (79%)] and remained good on follow-up. In 67 consecutive patients (95 studies), arteriovenous shunting to the lung ranged from 0.4 to 32% (mean, 6.2% +/- 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Despite our pragmatic approach in cases of atypical anatomy, largely due to our use of chemo-occlusion in cases with misperfusion of the liver, the rates of incomplete perfusion in our patients compare well with those reported by others [15][16][17][18] as regards both the whole series (6-24%) and those patients with ligation of aberrant arteries [18][19][20] (13-35%). More careful but time-consuming techniques have recently allowed complete perfusion in over 95% of patients [21,22].…”
Section: Discussionsupporting
confidence: 85%
“…Despite our pragmatic approach in cases of atypical anatomy, largely due to our use of chemo-occlusion in cases with misperfusion of the liver, the rates of incomplete perfusion in our patients compare well with those reported by others [15][16][17][18] as regards both the whole series (6-24%) and those patients with ligation of aberrant arteries [18][19][20] (13-35%). More careful but time-consuming techniques have recently allowed complete perfusion in over 95% of patients [21,22].…”
Section: Discussionsupporting
confidence: 85%
“…Kido and Ngan et al [5][6] found that AP shunts occur in 60% of patients with HCC, and Okuda et al [7] reported that marked AP shunts of the main, right, or left portal vein occur in 30% of HCC patients. Although the presence of small AP shunts does not necessarily preclude TACE therapy for unresectable HCC, larger AP shunts do interfere with TACE because anticancer drugs, either alone or mixed with iodized oil, easily pass through the shunts [8][9]. Conventional TACE causes extensive embolization of the portal vein and can therefore induce ischemia in extensive areas of nontumorous liver parenchyma in patients with HCC who have marked AP shunts [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kojiro [50] analyzed 106 resected HCCs less than 2 cm in diameter and found that nodular-type HCC was associated with microscopic portal invasion in up to 25% of cases. Although the presence of small arterioportal shunts does not necessarily preclude TACE therapy for unresectable HCC, larger arterioportal shunts do interfere with TACE because anticancer drugs, either alone or mixed with iodized oil, easily pass through the shunts [47, 48]. Conventional TACE causes extensive embolization of the portal vein and can induce extensive ischemia of nontumorous liver parenchyma in HCC patients with significant arterioportal shunts [46].…”
Section: How To Perform Tace For Advanced Hcc?mentioning
confidence: 99%